Analysis of the Effect of Operating Leverage and Financial Leverage on Companies Profitability Listed on Indonesia Stock Exchange - Asraf Asraf; Mia Muchia Desda (Yayasan Ilomata, 2020)
The purpose of this study was to explain the influence of the Degree of Operating Leverage (DOL) and Degree of Financial Leverage (DFL) on company profitability. The population in this study was consumer goods companies listed on the Indonesia Stock Exchange in 2017-2018, with 33 sample companies selected using purposive sampling. Method research was causality research and the data used is quantitative data. The company published a complete financial report from 2017 to 2018 which could be accessed through the Indonesian Stock Exchange Website and related company websites. The data were analyzed using the SPSS 21 application. The result shows that individual testing of DOL with profitability and DFL with profitability and joint testing of DOL and DFL with profitability found that DOL and DCL did not have a significant effect on the changes in company profitability (ROE and ROA) .